Traditional knowledge-based lifestyle interventions in the prevention of obesity and type 2 diabetes in Indigenous children in Canada: a systematic review protocol - Crawford, Rebecca (Syst Rev, 2019)
BACKGROUND: Approximately 50% of all youth-onset type 2 diabetes mellitus (T2DM) in Canada occurs in Indigenous children. In adults, cardiovascular disease is one of the leading causes of mortality in First Nations communities, and diabetes is a significant contributor to the risk of developing this disorder. The early onset of diabetes may predispose these children to premature cardiovascular disease and influence their longevity and quality of life. As a result, the implementation of culturally tailored obesity and T2DM primary prevention programs is vital. This systematic review aims to assess the effectiveness of existing traditional knowledge-based lifestyle intervention programs on preventing obesity and T2DM in Indigenous children in Canada. METHODS: We will conduct database searches in MEDLINE, Embase, PsycINFO, SPORTDiscus, CINAHL, Web of Science, Cochrane Database of Systematic Reviews, and the Cochrane Controlled Register of Trials. We will also conduct grey literature searches of central repository of trials (ClinicalTrials.gov), ProQuest Dissertations, Theses A&I, and Indigenous studies portal research tools. Reviewers will independently review titles, abstracts, and full-text articles retrieved from databases to assess potentially eligible studies, and relevant articles will be assessed for risk of bias and quality. The primary outcomes include the change in body mass index z-scores or a diagnosis of diabetes. The secondary outcomes include the change in measures of adiposity as well as lifestyle and metabolic profiles. A meta-analysis will be performed if two or more studies have used similar study designs, comparable intervention techniques , similar populations and measured similar outcomes. DISCUSSION: This review will provide a summary of current interventions to prevent obesity and T2DM in Indigenous children in Canada and help determine the gaps in the literature so that interventions can be developed to control the surge in pediatric T2DM in Indigenous communities. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42017072781 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13643-019-0961-4) contains supplementary material, which is available to authorized users.